1991
DOI: 10.1111/j.1365-3083.1991.tb01598.x
|View full text |Cite
|
Sign up to set email alerts
|

Allelic Variation in the TNF‐β Gene Does Not Explain the Low TNF‐β Response in Patients With Primary Biliary Cirrhosis

Abstract: Autoimmune disorders in humans are often associated with particular alleles of major histocompatibility genes. However, the chronic inflammatory liver disease primary biliary cirrhosis (PBC) has not been found to be correlated with certain haplotypes so far. Interestingly, an impaired production of tumour necrosis factor β (TNF‐β) upon mitogen stimulation was observed for PBC patients, especially in the immunologically active stages of the disease. Furthermore, the identification of alleles of the TNF‐β gene w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…All six SNPs identified in the IL-12 promoter were novel and the remaining three SNPs in the promoters of CTLA4, IL-10 and IL-6 had been previously identified [36,37]. A total of four intronic SNPs were detected in this study; one novel non-coding SNP was identified in intron 1 of IL-1· and three previously identified SNPs in intron 1 of LT· intron 2 of IL2i and intron 5 of Fas respectively [33,38,39].…”
Section: Noncoding Region Polymorphismsmentioning
confidence: 70%
“…All six SNPs identified in the IL-12 promoter were novel and the remaining three SNPs in the promoters of CTLA4, IL-10 and IL-6 had been previously identified [36,37]. A total of four intronic SNPs were detected in this study; one novel non-coding SNP was identified in intron 1 of IL-1· and three previously identified SNPs in intron 1 of LT· intron 2 of IL2i and intron 5 of Fas respectively [33,38,39].…”
Section: Noncoding Region Polymorphismsmentioning
confidence: 70%
“…A highly reliable approach, based on PCR-RFLP with amplification-created restriction sites (20), was developed to detect the polymorphism at positions -308 and -238 of the TNFa gene. An additional polymorphism in the first intron of the TNFP gene has been reported (19), with the two polymorphic alleles variably associated with high and low levels of TNFa secretion, depending on the population under investigation (12,21,22). Because of the possible functional significance of these polymorphisms, we investigated its association with the susceptibility to, and the disease profile of rheumatoid arthritis.…”
mentioning
confidence: 99%
“…Moreover, the homotrimeric form of lymphotoxin-α binds to the TNFα receptor [110]. Two of several variants identified in LTA, the IVS1+90A>G and Thr60Asn, are in tight LD and the intronic A-allele reduces LTA expression and increases TNF expression in vitro [111,112]. Of 65,671 SNP markers examined in a Japanese population the IVS1+90A>G and Thr60Asn were associated with myocardial infarction [113]; an observation that was subsequently replicated [114].…”
Section: Do Genes Encoding Proinflamma-tory Cytokines Play a Part In mentioning
confidence: 89%